2007
DOI: 10.1002/app.26252
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of vinyl substitute poly(silphenylene‐siloxane) via silyl hydride‐dialkoxysilane process

Abstract: The synthesis of vinyl-substituted silphenylene-siloxane polymer through B(C 6 F 5 ) 3 catalyzed polycondensation of 1,4-bis(dimethylsilyl)benzene and vinylmethyldimethoxysilane is described. H-NMR,29 Si-NMR, and UV spectroscopy indicate that the vinyl groups remain undamaged during the polycondensation reaction. No hydrosilylation side reaction is observed under the reaction conditions. The microstructure of the polymer is not perfectly alternating with a randomization of 20%. The temperature for 5% mass loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Tris­(pentafluorophenyl)­borane, B­(C 6 F 5 ) 3 , readily catalyzes the transfer of hydride ions from silicon to organic compounds. Thus, it is often used as a catalyst in the reduction of organic compounds by hydrosilanes. This borane is also a very active catalyst for hydride transfer reactions in organosilicon chemistry, which lead to the formation of siloxane or silylether bonds. Kawakami used B­(C 6 F 5 ) 3 to promote the polycondensation of hydrosilane with silanols. , It is also a very effective catalyst for the dehydrocarbon polycondensation of hydrosilanes with alkoxysilanes, , as well as a promoter of metathesis reactions between hydrosilane groups and alkoxysilane and metathetic dismutation reactions of oligohydrosiloxanes . The hydride transfer from silicon promoted by B­(C 6 F 5 ) 3 is also the main step in a new class of ring-opening polymerization reactions of cyclic siloxanes, which is proposed here to be named the hydride transfer polymerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Tris­(pentafluorophenyl)­borane, B­(C 6 F 5 ) 3 , readily catalyzes the transfer of hydride ions from silicon to organic compounds. Thus, it is often used as a catalyst in the reduction of organic compounds by hydrosilanes. This borane is also a very active catalyst for hydride transfer reactions in organosilicon chemistry, which lead to the formation of siloxane or silylether bonds. Kawakami used B­(C 6 F 5 ) 3 to promote the polycondensation of hydrosilane with silanols. , It is also a very effective catalyst for the dehydrocarbon polycondensation of hydrosilanes with alkoxysilanes, , as well as a promoter of metathesis reactions between hydrosilane groups and alkoxysilane and metathetic dismutation reactions of oligohydrosiloxanes . The hydride transfer from silicon promoted by B­(C 6 F 5 ) 3 is also the main step in a new class of ring-opening polymerization reactions of cyclic siloxanes, which is proposed here to be named the hydride transfer polymerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…At higher catalyst concentrations (∼1-5 mol%), hydrosilylation reactions may compete with the Piers-Rubinsztajn polycondensation reaction. 34,35 The reaction is almost instantaneous and is completed within a few minutes, but it was left to stir for 1 hour, in order to ensure the full conversion of reagents. Furthermore, high yields were obtained (>95%).…”
Section: Resultsmentioning
confidence: 99%
“…A similar reaction between vinylmethyldimethoxysilane and 1,4-bis(dimethylsilyl)- benzene was later performed to obtain a vinyl-substituted silphenylenesiloxane copolymer [ 102 ]. The P-R reaction also produced curable siloxane oligomers with a silphenylene or silbiphenylene unit and pendant vinyl and benzocyclobutene (BCB) functional groups ( Scheme 30 ) [ 103 ].…”
Section: Hydride Transfer From Si To C: Piers–rubinsztajn Reaction Le...mentioning
confidence: 99%
“…As a result of this competition, several R 3 Si-terminated oligomeric products with different numbers of Si-N-Si-O repeating units were obtained. Subsequently, they prepared polysiloxazanes with molecular weights ranging from 3.5 to 44.7 [ 102 ] and a relatively narrow molecular weight distribution by reacting 1,3-dimethoxytetraphenyldisilazane with SiH-terminated oligodimethylsiloxanes in the presence of TPFPB. The obtained results showed that the weakly basic nitrogen of tetraphenyldisilazane and the steric effect of four phenyl groups prevent it from forming a strong complex with TPFPB.…”
Section: Hydride Transfer From Si To C: Piers–rubinsztajn Reaction Le...mentioning
confidence: 99%